Exosomes Derived From Alveolar Epithelial Cells Promote Alveolar Macrophage Activation Mediated by miR-92a-3p in Sepsis-Induced Acute Lung Injury - Liu, Fen; Peng, Wei; Chen, Jiaquan; Xu, Zeyao; Jiang, Rong; Shao, Qiang; Zhao, Ning; Qian, Kejian (Frontiers in Cellular and Infection Microbiology, 2021)
Acute lung injury (ALI) induced by sepsis is characterized by disruption of the epithelial barrier and activation of alveolar macrophages (AMs), which leads to uncontrolled pulmonary inflammation. However, effective treatments for ALI are unavailable. The exact mechanism by which the initial mediator of alveolar epithelial cells (AECs) induces inflammation remains elusive. Here we investigated the roles of AEC-derived exosomes in AM activation and sepsis-induced ALI in vivo and in vitro. Cecal ligation and puncture (CLP) was utilized to establish septic lung injury model in rats. The effect of exosomal inhibition by intratracheal GW4869 administration on lung injury was investigated. To assess the effects of AEC-derived exosomes on ALI, we treated the rat alveolar epithelial cell line RLE-6TN with LPS to induce cell damage. Exosomes from conditioned medium of LPS-treated AECs (LPS-Exos) were isolated by ultracentrifugation. The miRNAs in LPS-Exos were screened by miRNA expression profile analysis. The effects of miR-92a-3p on the function of AMs were studied. We found that intratracheal GW4869 administration ameliorated lung injury following CLP-induced ALI. LPS-Exos were taken up by AMs and activated these cells. Consistently, administration of LPS-Exos in rats significantly aggravated pulmonary inflammation and alveolar permeability. Moreover, miR-92a-3p was enriched in LPS-Exos and could be delivered to AMs. Inhibition of miR-92a-3p in AECs diminished the proinflammatory effects of LPS-Exos in vivo and in vitro. Mechanistically, miR-92a-3p activates AMs along with pulmonary inflammation. This process results in activation of the NF-κB pathway and downregulation of PTEN expression, which was confirmed by a luciferase reporter assay. In conclusion, AEC-derived exosomes activate AMs and induce pulmonary inflammation mediated by miR-92a-3p in ALI. The present findings revealed a previously unidentified role of exosomal miR-92a-3p in mediating the crosstalk between injured AEC and AMs. miR-92a-3p in AEC exosomes might represent a novel diagnostic biomarker for ALI, which may lead to a new therapeutic approach.